The Complete genome sequence of Methanobrevibacter sp. AbM4. Issue 2 (March 2013) - Leahy, S.; Kelly, W.; Li, D.; Li, Y.; Altermann, E.; Lambie, S.; Cox, F.; Attwood, G.
Abstract Methanobrevibacter sp. AbM4 was originally isolated from the abomasal contents of a sheep and was chosen as a representative of theMethanobrevibacter wolinii clade for genome sequencing. The AbM4 genome is smaller than that of the rumen methanogenM. ruminantium M1 (2.0 Mb versus 2.93 Mb), encodes fewer open reading frames (ORFs) (1, 671 versus 2, 217) and has a lower G+C percentage (29% versus 33%). Overall, the composition of the AbM4 genome is very similar to that of M1 suggesting that the methanogenesis pathway and central metabolism of these strains are highly similar, and both organisms are likely to be amenable to inhibition by small molecule inhibitors and vaccine-based methane mitigation technologies targeting these conserved features. The main differences compared to M1 are that AbM4 has a complete coenzyme M biosynthesis pathway and does not contain a prophage or non-ribosomal peptide synthase genes. However, AbM4 has a large CRISPR region and several type I and type II restriction-modification system components. Unusually, DNA-directed RNA polymerase β′ and β″ subunits of AbM4 are joined, a feature only previously observed in some thermophilic archaea. AbM4 has a much reduced complement of genes encoding adhesin-like proteins which suggests it occupies a ruminal niche different from that of M1.